Mitigating Cyber-Threat in the Financial Industry of Bangladesh using Biometric based Public Key Infrastructure (PKI) with the Help of Digital Certification - Rifat Tasnim Anannya; Sifat Rahman Ahona (International Journal of Engineering and Management Research, 2020)
Information is such a thing which if misused, leaked or breached can lead to undesirable consequences. Financial institutions have a lot of data of their customers. These data’s are regarding customers’ personal information, transactions and many more which are highly sensitive. The entire system by which financial institutions such as – banks run, are required to be secured from cyber breach. As by breaching these systems’ can lead to financial disaster. The rapid growth of IT infrastructure is not only considered a convenient way for customers in many perspectives but also it point out the lack of skilled manpower in our country. In banking sector, ATM, E-money laundering are the domain where crime occurred most of the time. So, this paper focuses on developing a conceptual framework based on secondary sources which included publications, journal, books etc. regarding the problem of cyber-threat happening in Bangladesh. It describes how a financial institute can make safe transaction using biometric based public key infrastructure with the help of digital certificate.